METHODOLOGY FOR DETERMINING ENVIRONMENTAL INDICATORS OF OIL PRODUCTS TRANSPORTATION DURING WARTIME - Черкудінов, Володимир; Зеленько, Юлія; Безовська, Марина (SWorldJournal, 2025)
The article evaluates the levels of pollutant emissions from rail and road transport in order to determine their environmental safety during cargo transportation. The main attention is paid to comparing the specific and absolute emissions of carbon monox